Blue phase liquid crystals stabilized by graphene oxide modified with aminoalkyl group. (24th March 2018) - Zhao, Yuzhen; Qiao, Xun; Li, Kexuan; Ding, Siyi; Tian, Shaopeng; Ren, Huaping; Zhu, Min; Ma, Qiang; Zhao, Yang; Ban, Quanzhi; Miao, Zongcheng
ABSTRACT: In the present work, the graphene oxide/blue phase liquid crystal composites and long aminoalkyl chains functionalized graphene/blue phase liquid crystal composites were prepared by doping the additives into a blue phase exhibiting liquid crystal host. It is found that the blue phase temperature range could be widened by dispersing a small amount of functionalized graphene. It suggests that anisotropic two-dimensional flake nanoparticles may be of great usefulness for stabilizing blue phases.